Authorities pass bill with sweeping controls on social media - Amnesty International (Amnesty International, 2025)
The amendment Bill was presented in and passed by the National Assembly on 23 January 2025 and referred to the Standing Committee the next day by the Senate after backlash from opposition, media and civil society. The Prevention of Electronic Crimes Act passed in 2016 triggered widespread criticism from human rights organizations and activists for its potential for harmful impact on the right to freedom of expression and access to information in the country. The nine years since have confirmed these fears as journalists, human rights defenders and political opposition have been targeted under the law. Recently, the authorities have frequently imposed blanket bans on social media platforms and have blocked X, formerly Twitter, since February 2024.
Pakistan